Ten Years of Research on the Water-Energy-Food Nexus: An Analysis of Topics Evolution - Lazaro, Lira Luz Benites; Bellezoni, Rodrigo Augusto; Puppim de Oliveira, Jose Antonio; Jacobi, Pedro Roberto; Giatti, Leandro Luiz (Frontiers in Water, 2022)
This study explores how the concept and research on the water-energy-food (WEF) nexus has evolved over time. The research uncovers the key terms underpinning the phenomenon, maps the interlinkages between WEF nexus topics, and provides an overview of the evolution of the concept of WEF nexus. We analyzed published academic literature from the Scopus database and performed both qualitative and quantitative analyses using Natural Language Processing method. The findings suggest that the nexus approach is increasingly evolving into an integrative concept, and has been incorporating new topics over time, resulting in different methods for WEF nexus research, with a focus on interdisciplinary and inter-sectoral analyses. Through the five periods outlined, we have identified the nexus approach debate focused on the following predominant topics: i) Trend 1, (2012-2016) debates on WEF nexus for water management and natural resource security, ii) Trend 2, (2017-2018) linkages between the nexus, the sustainable development goals and green economy, iii) Trend 3, (2019) WEF nexus governance and policy integration, iv) Trend 4, (2020) application of the nexus concept on different scales, including regions, countries, watersheds, urban areas as well as other components coupled to the WEF nexus, and, v) Trend 5, (2021) climate change and urban nexus challenges.